2019
DOI: 10.1016/j.envpol.2018.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical food web structure drives trace element trophic transfer in Terra Nova Bay, Antarctica

Abstract: Despite in the last decades a vast amount of literature has focused on trace element (TE) contamination in Antarctica, the assessment of the main pathways driving TE transfer to the biota is still an overlooked issue. This limits the ability to predict how variations in sea-ice dynamics and productivity due to climate change will affect TE allocation in food webs. Here, food web structure of Tethys Bay (Terra Nova Bay, Ross Sea, Antarctica) was first characterised using carbon and nitrogen stable isotopes (δ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Lastly, a Mantel test was applied to assess if isotopic signatures of ITUs were predictive of the feeding links they made in the food web, considering both the identity and the relative contribution of each food source to each ITU. The Mantel test, as a permutation test for correlation between two distance or similarity matrices, allowed us to compare multivariate data with different similarity measures 79 . Here, the Euclidean distance and the Bray-Curtis dissimilarity were selected to quantify isotopic distances between ITUs and pairwise differences in feeding links respectively 72,79 .…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, a Mantel test was applied to assess if isotopic signatures of ITUs were predictive of the feeding links they made in the food web, considering both the identity and the relative contribution of each food source to each ITU. The Mantel test, as a permutation test for correlation between two distance or similarity matrices, allowed us to compare multivariate data with different similarity measures 79 . Here, the Euclidean distance and the Bray-Curtis dissimilarity were selected to quantify isotopic distances between ITUs and pairwise differences in feeding links respectively 72,79 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to deepen the knowledge of the source, diffusion, and effects of pollution in the Caspian Sea, future studies on this complex ecosystem should explicitly consider the spatial variability of anthropogenic pressures and the land use cover. Furthermore, as already observed in the Caspian Sea (Agah et al 2007) and in other coastal ecosystems (Signa et al 2019), the potential harmful effects of metal pollution on higher trophic levels should be further investigated. Therefore, for a highly anthropized ecosystem such as the Iranian Caspian Sea, determining the effects of metal and nutrient pollution on the food web is necessary for effective management and conservation actions.…”
Section: Discussionmentioning
confidence: 90%
“…This result was expected, as macroalgae absorb metals from water (Bonanno and Orlando-Bonaca 2018), while sediments represent the long-term repository in aquatic environments. The absence of correlation also indicates a divergent partitioning of metals from water to these two basal compartments of the food web and possibly implies different effects of the herbivore and detrital energy pathways on the transfer of metals to upper trophic levels (Mendoza-Carranza et al 2016;Signa et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the Ross Sea have demonstrated that sympagic production is readily incorporated into benthic biomass following sea-ice break-up (Norkko et al, 2007;Calizza et al, 2018), supporting between 30 and 80% of benthic secondary production (Wing et al, 2018). Accordingly, pulsed sympagic inputs during summer (Pusceddu et al, 2000(Pusceddu et al, , 2009 produce significant changes in the diet and trophic position of benthic taxa (Norkko et al, 2007;Calizza et al, 2018;Wing et al, 2018;Rossi et al, 2019), with cascade effects on predators at higher trophic levels (Leu et al, 2015;Poloczanska et al, 2016) and contaminant redistribution throughout the food web (Signa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%